SELF EFFICACY PASIEN JANTUNG KORONER SETELAH PERCUTANEOUS CORONARY INTERVENTION - Maysa Yutari Dewi; Wan Nishfa Dewi; Herlina Herlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Percutaneous Coronary Intervention (PCI) is an effort to improve coronary artery blood flow by destroying the plaque or atheroma which buried and disturbed the blood flow to the heart. Self Efficacy aims to improve patient’s expectation and quality of life. The  aim of this research is to identify self efficacy patient with Coronary Heart Disease (CHD) after having percutaneous coronary intervention. Descriptive study with cross sectional approach was used with 35 patient selected on inclusion criteria using purpossive sampling technique. Data were collected using cardiac self efficacy (CSE) questionnaire. Univariate analysis was used to describe characteristics of the patient and self efficacy using frequency distribution and percentage. Finding of this study show that the pasient have a good self efficacy for both subscale, with 28 patient (80%) in controlling symptoms and 20 patient (57%) at maintain function. Self efficacy can build patient’s confidence to keep and hold their health behavior to increase quality of life.Keywords: CHD, CSE, PCI, Self Efficacy